As Smart as a Human? Leveraging Models of Human Intelligence to Assess the Intelligence of Systems. Issue 1 (15th April 2020) - Brown, Barclay R.
ABSTRACT: As we evolve artificial and machine intelligence concepts, and consider their extension into intelligent systems, it becomes important to be able to assess the system's intelligence level. This assessment serves several important needs in systems engineering. First, it enables the tradeoff of system design alternatives based on a system's intelligence, along with other factors including cost and performance. Second, it influences system verification and validation methods. Lastly, it will help stakeholders specify the required system intelligence. Assessing or specifying the system's intelligence presents many challenges and difficulties similar to those faced by psychologists and neurologists in measuring the intelligence of human beings and animals. This article explores some human and animal intelligence assessment concepts and shows their application to assessing a system's intelligence.